Interlingual cover versions: how popular songs travel round the world. (2nd January 2019) - Susam-Saraeva, Şebnem
ABSTRACT: The article focuses on interlingual cover versions of popular songs – covers sung in a language other than the 'original'. Through a variety of disciplinary perspectives, including translation studies, adaptation studies and literary criticism, it examines an iconic song from a 'peripheral' country, which circulated the globe in the late 1990s and early 2000s. Tarkan and Sezen Aksu's Turkish hit Şımarık ('Spoilt') represents a noteworthy case of a cultural product in circulation across linguistic and cultural borders, with at least thirty four cover versions in twenty four languages. These covers were put into a wide range of contexts and to different uses in their new destinations, attesting to the fecundity afforded by this song. The article discusses concepts such as adaptation, palimpsest, parody, exoticism, iterability, globalisation and cosmopolitanism in relation to popular music covers. Its main objectives are to attract attention to the multiple factors underlying the production and reception of interlingual covers, to their prevalence and spread outside the Western European popular music scenes, where the current research concentrates, and to the diversity of approaches that can be taken in studying this phenomenon.